Removal of Phosphorus from Municipal Wastewater - Vidana Gamage, Kumudu Chathurani Dharmasena (Curtin University, 2016)
This study focused on the performance of phosphorus removal from municipal wastewater with chemical coagulation using alum. The best conditions for phosphorus removal was evaluated through bench scale laboratory studies using wastewater obtained from a wastewater treatment plant and laboratory prepared synthetic wastewater. The effect of various parameters including initial pH of the solutions, different alum dosing regimes, effect of DOC and alum dose on the efficiency of phosphorus removal was successfully evaluated.